High-dose therapy with peripheral blood stem cell transplantation results in a significant reduction of the haemopoietic progenitor cell compartment - Voso, Maria Teresa; Martin, Simona; Goldschmidt, Hartmut; Hohaus, Stefan; Haas, Rainer (British journal of haematology, 1996)
In order to study the effect of high-dose therapy with peripheral blood stem cell transplantation (PBSCT) on the haemopoietic reserve in man, the number and composition of bone marrow (BM) and peripheral blood (PB)-derived progenitor cells were examined in 137 cancer patients. In 45 patients, paired samples from BM and PB were obtained before PBSC mobilization and 6-27 months after transplantation. Following PBSCT, the proportion of CD34+ cells was significantly smaller than before mobilization (BM 1.99±0.24 versus 0.8±0.09, P<0.001), and no change was observed at several follow-up visits thereafter. The reduction was most pronounced for the primitive BM progenitor subsets such as the CD34+/DR− and CD34+/Thy-1+ cells. The impairment of hematopoiesis was also reflected by a significant reduction in the plating efficiency of BM and PB samples. No relationship was found between the decrease in the proportion of CD34+ cells and any particular patient characteristics, kind of high-dose therapy or the CD34+ cell content in the autograft. In conclusion, high-dose therapy with PBSC transplantation is associated with a long-term impairment of the haemopoietic system. The reduction in the number of haemopoietic progenitor cells is not associated with a functional deficit, as peripheral blood counts post-transplantation were normal in the majority of patients.